Optimization of bridges with short gap streamlined twin-box decks considering structural, flutter and buffeting performance. Issue 208 (January 2021) - Cid Montoya, M.; Nieto, F.; Hernández, S.; Fontán, A.; Jurado, J.A.; Kareem, A.
Abstract: While it is well known that the gap between twin-box decks is a key design variable that impacts the onset flutter velocity of a bridge, further research is required to ascertain how modifications in several bridge design variables affect other aeroelastic responses. This paper utilizes aero-structural optimization techniques for the design of long-span bridges with short gap twin-box decks considering simultaneously structural, flutter and buffeting constraints. The optimization helps to reduce the material volume of the structure while maintaining all the performance and safety requirements below the imposed thresholds. It has been found that the geometry of the individual box cross-section is an important feature for the control of the buffeting response, particularly the vertical acceleration. On the other hand, flutter and torsional buffeting constraints require designs with larger gap distance and alternative box geometries, leading to a trade-off between conflicting design demands. Hence, depending on the expected wind load conditions and the specific requirements of a particular project, an optimum aero-structural bridge design with a particular deck shape can be identified. The framework presented in this study is an effective tool to achieve sustainable and safe bridge designs that seeks a most efficient balance between all the design constraints. Highlights: The shape and size optimization problem for short gap twin-box deck bridges is addressed. Buffeting accelerations, flutter velocity, and structural responses are adopted as design constraints. Deck shape parametric studies of the buffeting response are presented. A long-span cable-stayed bridge is optimized for different buffeting and flutter thresholds. The buffeting response is highly dependent on the geometry of the deck boxes.